Enhancing density in hair transplant surgery: the role of tumescent injection in the recipient area in implanter technique – A randomized study - Gupta, Manan; Bhaskaran, Rajprakash; Krishnan, Murugesan (Aesthetic Medicine, 2025)
Background: Hair transplant surgery has undergone significant evolution - from FUT to FUE for follicular extraction, and from needles, slits, and implanter techniques to the sapphire technique for implantation. Despite these advances, achieving optimal density remains a challenge. In recent years, patients’ expectations for higher density have increased substantially, prompting surgeons to adopt techniques that are more effective and consistently deliver superior results. Objectives: To achieve density in hair transplant surgery mainly in FUE (Follicular Unit Extraction) + Implanter technique using Tumescent which has a composition of 100ml NS plus one ampule of Adrenaline at the recipient area using a spinal needle to increase the surface area. The author’s technique differs from the conventional needle-based approach and offers a distinct method for optimizing density. Materials & method: Patients willing to under Hair Transplant surgery by FUE + Implanter Technique where selected. The sample size was 100. Male patients with no associated medical co-morbidities where selected. A long 26-gauge spinal needle was used to inject the same tumescent solution in the recipient area. Implantation was performed using 1.2 or 1.0mm Inrut Implanters. A standard 1cm x 1cm box was placed over the image at the anterior region, where higher density is required, to assess density. Results: The hair density appreciated from 221 grafts per square inch in the non-tumescent group to 282 grafts per square inch in the tumescent group while the graft survival rate increased from 70.8% to 90.3%. Thus, increasing the patient satisfaction levels. Conclusion: Achieving optimal density in FUE combined with the implanter technique in hair transplant surgery remains a challenge. By increasing the surface area with tumescent solution, the popping effect during implantation is minimized. As the number of grafts per unit area increases, the resulting density also increases, serving as an indirect marker of success. This study presents a promising alternative for enhancing density; however, further comparative studies are needed to establish more precise treatment outcomes. The author has applied this method specifically to the implanter technique, rather than the conventional approach.